Clinical profile trial of patients cared with diabetes mellitus type 2 in a reversion program.: Perfil clínico de pacientes atendidos con diabetes mellitus tipo 2 en un programa de reversión - Torres Rodriguez, Eymard (2021)
Diabetes is a chronic disease that appears when the pancreas does not produce enough insulin or when the body does not use the insulin it produces effectively. Insulin is a hormone that regulates blood sugar. The effect of uncontrolled diabetes is hyperglycemia (increased blood sugar), which over time severely damages many organs and systems, especially nerves and blood vessels.